2017
DOI: 10.1186/s12955-017-0786-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home-based long-term care services on caregiver health according to age

Abstract: BackgroundCaregiver health is a crucial public health concern due to the increasing number of elderly people with disabilities. Elderly caregivers are more likely to have poorer health and be a care recipient than younger caregivers. The Taiwan government offers home-based long-term care (LTC) services to provide formal care and decrease the burden of caregivers. This study examined the effects of home-based LTC services on caregiver health according to caregiver age.MethodsThis cross-sectional study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 34 publications
0
37
0
4
Order By: Relevance
“…In addition, despite the recognized need for some support for the family caregiver 10 , 14 , 16 - 18 , the formal support network is still very restricted. In Europe, care was more prevalent among women aged 50–59, unemployed ones, especially those who do household chores, and religious persons 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, despite the recognized need for some support for the family caregiver 10 , 14 , 16 - 18 , the formal support network is still very restricted. In Europe, care was more prevalent among women aged 50–59, unemployed ones, especially those who do household chores, and religious persons 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The act of caring is a stressful experience that can affect the physical and mental health of the caregiver 18 , despite their health conditions 12 , 13 , 16 and their moment at the course of life. The relationship of the caregiver with a dependent person reduces their chances of keeping a healthy life, deprives them of social contacts, compromises their physical and psychological well-being 17 , 18 , and also exposes them to long-term care (LTC).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a systematic review and meta-analysis of 32 randomized controlled trials showed that psychoeducation was associated with a significant decrease in global morbidities and perceived burden in family carers of people with psychosis ( 42 ). Another cross-sectional study further found in almost 600 participants that home nursing care had a significant and positive impact on self-rated health in caregivers aged 65 years or older ( 43 ). Finally, a study of 39 patients with dementia and their caregivers revealed that there was a positive relationship between institutional respite periods, total sleep time per night, total time in bed per night, and improvements in subjective sleep quality ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported survey [41] has found that the need for continuous nursing of patients with moderate and severe TBI ranked rst, and home visiting is welcomed by all the respondents. But at present, because the family visits are affected by geographic location and human resources, the coverage of home-based nursing care is very limited [42]. In addition, the domestic community nursing service is relatively lacking in China, and the cooperative communication mechanisms between hospital and community are not perfect, and it cannot provide effective home care for patients, the patients' medical care service needs have not been met [43].…”
Section: Discussionmentioning
confidence: 99%